Territorial governance in the Marrakech-Safi region: issues and challenges of decentralization and deconcentration policies - SALHI, SALIMA (Geografares, 2025)
The study focuses on the implementation of decentralization and deconcentration reforms in the Marrakech-Safi region. Through an analysis of territorial governance, carried out in the field with local players, as well as spatial and statistical analyses, the study highlights the difficulties associated with coordination between the various players, the slow political maturation of elected representatives, and the absence of effective accountability mechanisms. Regionalization, decentralization and deconcentration policies aim to transfer powers to local authorities. This article analyzes the implementation of these reforms, highlighting the gaps between the theoretical principles of the laws and their application in the field, particularly in the management of territorial projects. The study insists on the need for genuine political will and an overhaul of political practices to establish effective territorial governance, adapted to the specific characteristics of the regions, particularly Marrakech-Safi. Despite ambitious reforms, the study underlines that Morocco still faces many challenges in establishing territorial governance that reduces inequalities and promotes balanced development, particularly in high-potential regions such as Marrakech-Safi.